MISCONCEPTION DIAGNOSTIC IN QUANTUM NUMBER MATERIALS AND ELECTRON CONFIGURATION - Mohammad Agus Prayitno; Deni Ebit Nugroho (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
The purpose of this research is to design a four-tier diagnostic test instrument on electron configurations and quantum numbers that can be used to analyze misconceptions. The four-level diagnostic test instrument is an assessment instrument that functions to assess students' conceptual comprehension in understanding a subject matter. The four tier test has four levels, namely knowledge questions, confidence questions in completing questions, reasons for answering questions, and confidence in giving reasons. This study uses a descriptive qualitative method with the stages of analyzing the problem, collecting data, product design, validating the design, and conducting instrument trials. The results showed that the designed diagnostic instruments were feasible and reliable. Instrument test results indicate that indicator a) determines the magnitude of the four quantum numbers (n,ℓ,mℓ, ms) in an orbital; b) identify the characteristics and functions of the azimuth quantum number (ℓ); c) determine the spin magnetic quantum number (ms) of the electron in the orbital; and d) determine the spin magnetic quantum number (ms) of a single electron in an orbital, which is the most misunderstood.